Rehabilitation and Renewal of Mediterranean Structures. The Utopic Landscape of Algarve - Bragança dos Santos, Carlos (REGION, 2018)
One of the remarkable features of Mediterranean landscapes is the terraced land frame, usually supported by dry stone walling. The terraces, property division walls, pathways and traditional paths design a network compartmentalization that defines landscape identity. The informational content, aesthetic quality, ecological and cultural values allowed by this articulated construction are particularly important at coastal zones with intense human impact. On the Algarve, the hills displayed by such structures form the background scenario of an urban-touristic system. This paper aims to interrelate ecological, aesthetic, symbolic, socio-economic and political aspects that influence the spatial distribution and image of the terraces. The values that local people may assign to their landscapes will determine the acknowledgement of the structural elements under analysis, but the role of tourists must be seriously take into account. Beyond nostalgic solutions, one must prospect the future of the dry stone walling structure into the diversity of possible solutions for a sustainable landscape development, which enhances the living part of an inseparable unit that includes the densest urbanized areas with less ecological functions. We call such unit the urban-touristic region of Algarve and, therefore, we try to use landscape as an instrument of knowledge and acknowledgement of regional spaces.